Research output in radioactive waste management based on non-conventional literature. (1st January 2014) - Swarna, T.; Rane, Madhuri S.; Aroskar, Ujwala V.; Prabhu, Anjali; Bhanumurthy, K.
This paper identifies the research paradigms in the area of radioactive waste management based on the technical reports retrieved from the International Nuclear Information System (INIS) from 1970 to 2012. The aim is to determine the volume of research output, the countries involved in the research; collaboration network has been studied at the micro level (individuals) and the macro level (countries). Bibliometric and social network analyses were employed to achieve the results.